ANALISIS GAYA KEPEMIMPINAN, INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. SARANA TANI PRATAMA KABUPATEN JEMBRANA-BALI - Putu Lidia Marini (Bajang Institute, 2023)
This study aims: 1) To analyze the influence of leadership style on employee performance, on PT Sarana Tani Pratama, Jembrana-Bali, 2) To analyze the incentives and motivation on employee performance at PT Sarana Tani Pratama Jembrana-Bali, 3) To analyze variable the dominant influence on the performance of employees at PT Sarana Tani Pratama, Jembrana, Bali. The method used was survey by using instrument list of questions or the questionnaire as a data collection tool. Patterns of influence that will be revealed in this study was the influence of leadership style, Incentives and Work Motivation on Employee Performance At PT Sarana Tani Pratama, Jembrana – Bali. Results of this study prove that: (1) style of leadership, incentives and motivation simultaneously affect the performance of employees, (2) style of leadership, incentives and motivation partially influence on employee performance, (3) leadership style dominant influence on employee performance